Prevalence findings from a community-based female genital fistula screening program in Bangladesh - Ghose, Lucky; Huda, Sk Nazmul; Tripathi, Vandana (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This paper presents the findings of a community-based program to conduct house-to-house fistula screening in a district in Bangladesh. Methods: The USAID-supported Fistula Care Plus (FC+) project in Bangladesh purposively selected a district (Faridpur) for fistula programming. Fistula screening was integrated into the house-to-house activities of a NGO, active in community health. From July to December 2016, all households were reached by field staff for identification of any possible fistula cases using a four questions checklist. Suspected fistula cases were referred to community based fistula diagnosis events at regular intervals. Results: Among 0.5 million women, using the 4Q checklist, field workers identified 604 women as suspected fistula or perineal tear with fecal incontinence cases. Of these, 149 cases were clinically confirmed. The prevalence of fistula was 0.3/1000 ever-married women in the district. Conclusion: The fistula prevalence documented in Faridpur through this screening partnership is much lower than that reported in a 2003 UNFPA/EngenderHealth survey in Bangladesh (1.69/1000 ever-married women). This difference in district-level prevalence also suggests the value of local data in the development and implementation of fistula programs.